Inclined wall plumes in porous media - Shu, Jian Jun (2011)
We present a numerical solution of the natural convection from inclined wall plumes which arise from a line thermal source imbedded at the leading edge of an adiabatic plate with arbitrary tilt angle between 0 and pi/2, and embedded in a fluid-saturated porous medium. An appropriate transformation of the governing boundary-layer equations is proposed and a very efficient novel numerical solution is proposed to obtain rigorous numerical solutions of the transformed nonsimilar equations over a wide range of tilt angle from the vertical to the horizontal. Graphs are presented showing the effect of the tilt angle on the velocity and temperature profiles, as well as on the wall velocity and wall temperature. As far as we know, this problem has not yet been studied in the available literature.